Human Umbilical Cord Blood-Derived CD133+CD34+ Cells Protect Retinal Endothelial Cells and Ganglion Cells in X-Irradiated Rats through Angioprotective and Neurotrophic Factors - Chen, Siyu; Li, Minghui; Sun, Jianguo; Wang, Dan; Weng, Chuanhuang; Zeng, Yuxiao; Li, Yijian; Huo, Shujia; Huang, Xiaona; Li, Shiying; Zou, Ting; Xu, Haiwei (Frontiers in Cell and Developmental Biology, 2022)
Radiation retinopathy (RR) is a common complication following radiation therapy of globe, head, and neck malignancies, and is characterized by microangiopathy, neuroretinopathy, and the irreversible loss of visual function. To date, there is no effective treatment for RR. Stem cells have been clinically used to treat retinal degeneration. CD133+CD34+ cells from human umbilical cord blood (hUCB-CD133+CD34+ cells), a subpopulation of hematopoietic stem cells, were applied to determine their protective efficacy on irradiated rat retinas. After X-ray irradiation on the retinas, rats were intravitreally injected with hUCB-CD133+CD34+ cells. Transplantation of hUCB-CD133+CD34+ cells prevented retinal dysfunction 2 weeks post-operation and lasted at least 8 weeks. CD133+CD34+ cells were distributed along the retinal vessel and migrated to the ganglion cell layer. Moreover, grafted CD133+CD34+ cells reduced the apoptosis of endothelial and ganglion cells in irradiated rats and increased the number of survived CD31+ retinal endothelial cells and Brn3a+ ganglion cells at 2 and 4 weeks, respectively, post-operation. Co-culturing of CD133+CD34+ cells or supernatants with irradiated human retinal microvascular endothelial cells (hRECs) in vitro, confirmed that CD133+CD34+ cells ameliorated hREC apoptosis caused by irradiation. Mechanistically, we found that angioprotective mediators and neurotrophic factors were secreted by CD133+CD34+ cells, which might attenuate irradiation-induced injury of retinal endothelial cells and ganglion cells. hUCB-CD133+CD34+ cell transplantation, as a novel treatment, protects retinal endothelial and ganglion cells of X-irradiated rat retinas, possibly through angioprotective and neurotrophic factors.